Por um abandono crítico de homo sacer: ou dos não ditos eurocêntricos e coloniais da filosofia política de Giorgio Agamben - Nobre, Emanuel Lucas de Sousa (2024)
The present work set out to trace a possible itinerary through the key points of the political philosophy project “Homo Sacer”, composed of nine writings published over three decades by the Italian philosopher Giorgio Agamben (1942). However, this itinerary sought not to have a merely exegetical nature, but a critical-exegetical one: the examination and reproduction of Agamben’s theses did not constitute ends in themselves, but means for carrying out a critical abandonment of “Homo Sacer”, that is, the exposure of the limits and contradictions that, underlyng the project, prevent its full realization. To build such a path, this work was divided into two fronts, the first consisting of the exposure of the main programmatic core of the project: the genealogy of Western Power and the possibilities of overthrowing it. The second part, in turn, took shape from the objective of demonstrating of the colonized Global South in the philosophy of history of “Homo Sacer”. That such obfuscation occurs not throught the operation of the glorious device of Eurocentrism, led us to seek, in the colonial tradition, the non-Eurocentric reading keys that Agamben could not reach; either to understand the catastrophe or to outline strategies to stop it.